Palynological analysis of unifloral commercial honeys - Rodríguez de la Cruz, David; Sánchez Reyes, Estefanía; Sánchez Durán, Silvia; Sánchez Sánchez, José (Botanica Complutensis, 2013)
Twenty eight honey samples labelled as monofloral and Spanish were studied by means of quantitative and qualitative methods: orange blossom (11), eucalyptus (10) and rosemary (7). Quantitative analysis displayed a higher number of botanical elements in eucalyptus honeys (354497/10 g of honey) than in orange blossom and rosemary honeys (100111 y 76705, respectively). Qualitative study showed high pollen richness in rosemary and orange blossom honyes (an average of 38 and 41 types of pollen, respectively), lower in the case of eucalyptus honeys (34). All of these types of pollen belonged to Iberian species, except in two samples (orange blossom and eucalyptus) with pollen grains from South America flora. Rosemary honeys reached 10% of Salvia verbenaca type, whereas one and two samples of orange blossom and eucalyptus did not exceed 10% and 70% of Citrus sinensis y Myrtus communis types, respectively.
Keywords: pollen; honey; origin; quality control